Applicability of dynamic facilitation theory to binary hard disk systems - Isobe, Masaharu; Keys, Aaron S.; Chandler, David; Garrahan, Juan P. (American Physical Society, 2016)
We numerically investigate the applicability of dynamic facilitation (DF) theory for glass-forming binary hard disk systems where supercompression is controlled by pressure. By using novel efficient algorithms for hard disks, we are able to generate equilibrium supercompressed states in an additive nonequimolar binary mixture, where microcrystallization and size segregation do not emerge at high average packing fractions. Above an onset pressure where collective heterogeneous relaxation sets in, we find that relaxation times are well described by a “parabolic law” with pressure. We identify excitations, or soft spots, that give rise to structural relaxation and find that they are spatially localized, their average concentration decays exponentially with pressure, and their associated energy scale is logarithmic in the excitation size. These observations are consistent with the predictions of DF generalized to systems controlled by pressure rather than temperature.